2021
DOI: 10.3389/fimmu.2021.636238
|View full text |Cite
|
Sign up to set email alerts
|

PSGL-1 Immune Checkpoint Inhibition for CD4+ T Cell Cancer Immunotherapy

Abstract: Immune checkpoint inhibition targeting T cells has shown tremendous promise in the treatment of many cancer types and are now standard therapies for patients. While standard therapies have focused on PD-1 and CTLA-4 blockade, additional immune checkpoints have shown promise in promoting anti-tumor immunity. PSGL-1, primarily known for its role in cellular migration, has also been shown to function as a negative regulator of CD4+ T cells in numerous disease settings including cancer. PSGL-1 is highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 185 publications
(221 reference statements)
2
26
0
Order By: Relevance
“…Naïve T cells lack these modifications and are thus unable to bind selectins, but can acquire selectin binding capacity during effector differentiation ( 11 ), although expression is typically transient. On T cells, however, PSGL-1 can engage additional ligands in the absence of, or independently of selectin binding ( 12 ). These include the lymphoid tissue chemokines, CCL19 and CCL21 ( 13 ), which regulate the entry and positioning of T cells and dendritic cells in secondary lymphoid organs ( 14 ), and VISTA (V-type immunoglobulin domain-containing suppressor of T cell activation) ( 15 ), a negative regulator of T cell responses, which is primarily expressed on myeloid cells ( 16 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Naïve T cells lack these modifications and are thus unable to bind selectins, but can acquire selectin binding capacity during effector differentiation ( 11 ), although expression is typically transient. On T cells, however, PSGL-1 can engage additional ligands in the absence of, or independently of selectin binding ( 12 ). These include the lymphoid tissue chemokines, CCL19 and CCL21 ( 13 ), which regulate the entry and positioning of T cells and dendritic cells in secondary lymphoid organs ( 14 ), and VISTA (V-type immunoglobulin domain-containing suppressor of T cell activation) ( 15 ), a negative regulator of T cell responses, which is primarily expressed on myeloid cells ( 16 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We cloned human SELPLG cDNA in a vector containing GFP for expression in EL4.2 cells. Despite differences in amino acid sequence, human and mouse PSGL-1 are functionally conserved, as supported by reports showing PSGL-1 cross-species interactions with selectins [29] , [30] , [31] . After transfection of GFP-expressing empty and PSGL-1-expressing plasmids and serial sorting and culturing of GFP-positive cells (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Finally, a recent publication extensively reviewed the role of PSGL-1 in the development of neoplastic disease. The authors reported that blocking the CD4 + T-cell’s PSGL-1 pathway could possibly be utilized as a novel cancer therapeutic approach to treat tumors ( 98 ). Indeed, PSGL-1 activation in the tumor microenvironment can promote CD4 + T-cell exhaustion pathways, which promotes tumor development.…”
Section: Recognized Psgl-1 Functions During Infections And/or Inflammationmentioning
confidence: 99%
“…Secondly, PSGL-1 is an HIV restriction factor, and as such, its expression is triggered by interferon-γ, an immunomodulatory cytokine whose role in innate immunity in HIV infection has only begun to be elucidated ( 109 , 110 ). Additionally, IL-12 (using Th1 cells from mice) ( 98 ), soluble CD40 ligand (sCD40L, using monocytes from HIV negative donor) ( 104 ), and glutamate (using monocytes from HIV negative donor) ( 104 ) have been proven to be capable of inducing PSGL-1 expression ex vivo . Thus, interferon-γ or IL-12 administration in combination with strategies such as ART, immunotherapy, and gene therapy may provide substantial improvement in the immune responses of HIV-infected individuals.…”
Section: Psgl-1 and Hiv-1 Infectionmentioning
confidence: 99%
See 1 more Smart Citation